2021
DOI: 10.1002/bab.2176
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin E at a high dose as an anti‐ferroptosis drug and not just a supplement for COVID‐19 treatment

Abstract: The novel coronavirus (SARS-CoV-2) was first identified in humans in late 2019. As of January 2021, over 100 million cases of coronavirus disease 2019 were confirmed worldwide, with over 2% of death. It is estimated 30% of the population were to get infected. There are several vaccines with emergency use authorization worldwide. Currently, vaccination started globally, but its longterm effectiveness is still under clinical trial. 1 The critical question is how to treat patients infected with SARS-CoV-2. Initi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 11 publications
(19 reference statements)
1
24
0
1
Order By: Relevance
“…Finally, we investigated the persistence of apoptotic and ferroptotic activities of SIM and SIM-CB in the presence of vitamin E which is a potent antioxidant and a ferroptosis inhibitor. [25][26][27] Clarifying the cytotoxic properties of SIM-loaded cubosome may consequently provide a good opportunity to further optimize the off-label activity of SIM-CB as a promising systemic (intravenous) anticancer agent against persistent breast cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, we investigated the persistence of apoptotic and ferroptotic activities of SIM and SIM-CB in the presence of vitamin E which is a potent antioxidant and a ferroptosis inhibitor. [25][26][27] Clarifying the cytotoxic properties of SIM-loaded cubosome may consequently provide a good opportunity to further optimize the off-label activity of SIM-CB as a promising systemic (intravenous) anticancer agent against persistent breast cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Vitamin E supplementation at 500 mg/kg may act as a treatment drug to inhibit ferroptosis in COVID-19 patients and decline ferroptosis damages to multiple organs, namely the lungs, kidneys, liver, gut, heart and nervous system. It reduces the ferric iron center in 15-lipoxygenase to inactive ferrous (Fe 2+ ), resulting in 15-lipoxygenase inhibition and preventing lipid hydroperoxides formation [ 137 ].…”
Section: Major Food Groups Efficient In Covid-19 Pathogenesismentioning
confidence: 99%
“…This can lead to ferroptosis, a programmed cell death indicated by lipid peroxides and depending on the iron level in the body. Current clinical studies revealed that vitamin E has the potential to inhibit ferroptosis and can be exploited as an anti-ferroptosis drug [196].…”
Section: Antiviral Therapiesmentioning
confidence: 99%